(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to determine how internal control and fraud detection are and how internal controls affect fraud detection. The factors tested in this study were internal controls as independent variables and detection of fraud as dependent variables. The research methods used in this research are a descriptive and an exploitation method of research. In order to achieve the objectives of this study, a questionnaire was developed and distributed to all parts related to the internal control of several state-owned enterprises in Bandung City. The total number of questionnaires distributed was 100, of which 70 were returned and were valid for data analysis. Based on the results of the statistical analysis, the study indicated that internal control and fraud detection in several state-owned banks in the city of Bandung belong to the category of good. These results indicate that internal control has an important role in detecting fraud in state-owned banks. So, the higher the effectiveness of internal control, the higher the fraud detection also.